Adult Students in the European Higher Educational Environment - N. G. Gordiyenko (Образование и наука)
The paper considers the issue of accessibility of higher education for adults – the people of various ages and social status. The author analyzes the educational policy of the European Union and its different members, and demonstrates the priority of the given issue. The Bologna agreement involves the reforms aimed at guaranteeing the lifelong education at any level.The interest to the adults education in the European Union results from the rising education requirements in the labor market; tough demographic situation and aging of professionals; redistribution of young people’s educational preferences; prolonged educational programs; flexible and consistent adult education policies in the European Union. Various approaches to interpreting a definition of the adult student are analyzed; classification according to students’ motivation and social status is given.